Analisis Faktor-Faktor yang Memengaruhi Tax Avoidance Pada Perusahaan Sektor Manufaktur - Natrion; Sianturi, Heriston; Sidauruk, Tagor Darius (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
Since taxes are the state's main source of income, the government must work to make its revenue more efficient. However, as taxes are a burden that taxpayers must pay efficiently, the purpose of this study is to examine factors that affect tax evasion in manufacturing companies that are listed on the Indonesia Stock Exchange between 2020 and 2023. Secondary data from the 2020–2023 annual financial reports of manufacturing businesses listed on the Indonesia Stock Exchange are used in this kind of quantitative study. Purposive sampling with certain criteria is used in the sampling technique. Multiple linear regression is used in the data analysis technique to evaluate the relationship between the independent and dependent variables. Transfer pricing, audit committees, and capital structures, in part, have little bearing on tax evasion. Institutional ownership, meanwhile, has some bearing on tax evasion. Transfer pricing, institutional ownership, audit committees, and capital structure all have an impact on tax evasion at the same time.